Energy dependence of morphologies on photoresist surfaces under Ar+ ion bombardment with normal incidence - Yang, Gaoyuan; Hirsch, Dietmar; Li, Jinyu; Liu, Ying; Frost, Frank; Hong, Yilin (Applied surface science, 2020)
[Display omitted] •Energy dependence of resist morphology under ion bombardment is demonstrated.•Light molecules in organic resist were enriched by ion bombardment.•Ion energy shows great potential for modulating chemistry and morphology.•Nanoholes were formed on organic resist in a wide ion energy range.•Morphology evolution is preliminarily explained using existing theoretical models. The energy dependence of nanostructures on a photoresist produced by ion bombardment (IB) under normal incidence is studied through atomic force microscopy and time-of-flight secondary ion mass spectroscopy (ToF-SIMS). The energy-dependent morphology evolved from weak islands via nanoholes to a smooth surface on the resist; in particular, nanoholes were produced for a broad energy range of 300–550 eV. The enrichment of light components in the surface layer of the irradiated resist was illustrated owing to the strong decomposition of the photoresist by IB. The energy dependence of the morphologies is explained according to the ToF-SIMS characterization and the existing theoretical models of IB, which is an IB-induced synergy of chemical variation and sputtering. This study extends the IB in inorganic materials into an organic-multicomponent photoresist and provides new insights into the experimental evidence for nanoholes and possible parameters to improve the relevant theoretical model.